Lexical Processing in Bilingual Children: Evidence from Masked Phonological Priming - Gopi Shankar R; Jasmine Malik; Jayashree C Shanbal (Journal of All India Institute of Speech and Hearing, 1970)
Earlier, the general idea was that bilinguals had two mental lexicons: one for the first language and one for the second. In addition, a language switch mechanism controlled which lexicon was active. In recent years, however, evidence has accumulated showing that the initial stages of visual word recognition are largely language independent and that the assumption of independent lexicons may not be true. The aim of the present study is to explore visual word recognition in bilinguals through a masked phonological priming experiment. The participants consisted of 30 Kannada-English bilingual children in the age range of 10-12 years. The test material consisted of a total of 40 words in Kannada and 40 words in English. These were studied in 4 different priming conditions which included 10 semantically related prime (SR), 10 semantically unrelated prime (SUW), 10 non-words (NW) and 10 orthographically related nonword prime (OR). The findings of the study are further discussed with evidence from language-selective access models of bilingual word processing and phonological models of lexical processing.